2021
DOI: 10.1002/1878-0261.13088
|View full text |Cite|
|
Sign up to set email alerts
|

hnRNP‐A1 binds to the IRES of MELOE‐1 antigen to promote MELOE‐1 translation in stressed melanoma cells

Abstract: The major challenge in antigen-specific immunotherapy of cancer is to select the most relevant tumor antigens to target. To this aim, understanding their mode of expression by tumor cells is critical. We previously identified a melanoma-specific antigen, melanoma-overexpressed antigen 1 (MELOE-1) -coded for by a long non-coding RNA -whose internal ribosomal entry sequence (IRES)-dependent translation is restricted to tumor cells. This restricted expression is associated with the presence of a broad specific T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Additionally, hnRNPA1 was involved in tumor immune responses as well. Ectopic hnRNPA1 elicited thapsigargin-induced endoplasmic reticulum (ER) stress, promoted translation of specific melanoma-overexpressed antigen 1 (MELOE-1), and further enhanced recognition of melanoma cells by MELOE-1-specific T-cell clone, improving their immune efficacy [ 55 ]. Moreover, hnRNPA1 played an important role in mediating hormone homeostasis.…”
Section: The Roles Of Hnrnpa/b In Cancers: Molecular Mechanisms and C...mentioning
confidence: 99%
“…Additionally, hnRNPA1 was involved in tumor immune responses as well. Ectopic hnRNPA1 elicited thapsigargin-induced endoplasmic reticulum (ER) stress, promoted translation of specific melanoma-overexpressed antigen 1 (MELOE-1), and further enhanced recognition of melanoma cells by MELOE-1-specific T-cell clone, improving their immune efficacy [ 55 ]. Moreover, hnRNPA1 played an important role in mediating hormone homeostasis.…”
Section: The Roles Of Hnrnpa/b In Cancers: Molecular Mechanisms and C...mentioning
confidence: 99%
“…Common ORFs are defined as the DNA sequence found between the start (ATG or AUG) and stop codons (TAG or TGA) ( Sieber et al, 2018 ), whereas sORFs typically possess less than 300 nucleotides in length, and longer sORFs are more likely to be translated ( Pueyo et al, 2016 ; Orr et al, 2020 ). It has also been found that regulatory elements upstream of ORFs, e.g., internal ribosome entry site (IRES), N6-methyladenosine (m6A) methylation conserved sites, can mediate micropeptide translation ( Wu P et al, 2020 ; Charpentier et al, 2022 ). IRES elements are important regulatory RNA sequences that do not rely on 5' cap for translation, which mostly occur in the 5' untranslated region (5' UTR) upstream of the ORF controlled by IRES ( Zhao et al, 2018 ).…”
Section: Translational Mechanisms Of Lncrna-encoded Micropeptidesmentioning
confidence: 99%
“…Recent studies have found that knockdown of lncRNA-NKILA in cytotoxic T lymphocytes regulates the sensitivity of T cells to activation-induced cell death by reducing the expression of NF-κB, thereby effectively inhibiting the growth of patient-derived xenografts from breast cancer in mice ( 123 ). Melanoma-overexpressed antigen 1 (MELOE-1), which is encoded by a long noncoding RNA in tumor cells and can specifically improve the tumor antigen of MELOE-1 through thapsigargin drug stimulation, enhances the ability of T cells to recognize melanoma cells ( 124 ). Additionally, exosome-related therapy can inhibit tumor progression by regulating the immune system of the organism.…”
Section: Lncrnas As Potential Therapeutic Targetsmentioning
confidence: 99%